Pengaruh Ekonomi, Pengetahuan, dan Pelayanan Petugas Kesehatan terhadap Kunjungan Pemeriksaan Kehamilan di Wilayah Kerja Puskesmas Cilebut Tahun 2022: Economic Influence, Knowledge, and Services of Health Officers on Pregnancy Examination Visits in the Working Area of Cilebut Health Center in 2022 - Pratiwi, Dessy Anggryani; Purwani Pujiati; Ernita Prima Noviyani (Dohara POAJ, 2025)
Introduction: A pregnancy check-up visit is a visit by a pregnant woman to a midwife or doctor as early as possible since she feels she is pregnant to get pregnancy services/care. Nationally in 2010 the K1 coverage was 95.26% and the K4 coverage was 85.56%. The economy, knowledge, and services of health workers are factors that influence prenatal care visits. This study aims to determine the effect of the economy, knowledge, and services of health workers on antenatal care visits in the working area of ​​the Cilebut Health Center in 2022. Methods: The research method is a quantitative cross-sectional approach. The population in this study were 150 pregnant women who were in the working area of ​​the Cilebut Health Center. The research sample was determined based on the simple random sampling technique with the calculation of the slovin formula so that a sample of 60 respondents was obtained. Results: The results showed that there was an influence of economics (p-value 0.035), knowledge (p-value 0.000), and health worker services (p-value 0.000) on antenatal care visits. Discussion: The conclusion of the study is that there is an economic influence, knowledge and services of health workers on antenatal care visits in the working area of ​​the Cilebut Health Center in 2022. Suggestions for pregnant women are expected to increase knowledge and understanding for pregnant women so that they are more disciplined in conducting prenatal check-ups. Keywords : Economy, Knowledge, Pregnancy Check-up Visits, Services of Health Officers